Coordination between MIDASIN 1-mediated ribosome biogenesis and auxin modulates plant development. (21st January 2021) - Li, Ke; Zhou, Ximeng; Sun, Xueping; Li, Guanghui; Hou, Lei; Zhao, Shuzhen; Zhao, Chuanzhi; Ma, Changle; Li, Pengcheng; Wang, Xingjun
Abstract: Ribosomes are required for plant growth and development, and ribosome biogenesis-deficient mutants generally display auxin-related phenotypes. Although the relationship between ribosome dysfunction and auxin is known, many aspects of this subject remain to be understood. We previously reported that MIDASIN 1 (MDN1) is an essential pre-60S ribosome biogenesis factor (RBF) in Arabidopsis. In this study, we further characterized the aberrant auxin-related phenotypes of mdn1-1, a weak mutant allele of MDN1 . Auxin response is disturbed in both shoots and roots of mdn1-1, as indicated by the DR5:GUS reporter. By combining transcriptome profiling analysis and reporter gene detection, we found that expression of genes involved in auxin biosynthesis, transport, and signaling is changed in mdn1-1 . Furthermore, MDN1 deficiency affects the post-transcriptional regulation and protein distribution of PIN-FORMED 2 (PIN2, an auxin efflux facilitator) in mdn1-1 roots. These results indicate that MDN1 is required for maintaining the auxin system. More interestingly, MDN1 is an auxin-responsive gene, and its promoter can be targeted by multiple AUXIN RESPONSE FACTORs (ARFs), including ARF7 and ARF19, in vitro . Indeed, in arf7 arf19, the auxin sensitivity of MDN1 expression is significantly reduced. Together, our results reveal a coordination mechanism between auxin and MDN1-dependent ribosome biogenesis for regulating plant development. Abstract : Deficiency in MDN1 -associated ribosome biogenesis alters the global auxin system, and auxin, in turn, regulates MDN1 expression through multiple ARFs, implying coordination between ribosome biogenesis and auxin for regulating plant development.